Hands-on analysis of using large language models for the auto evaluation of programming assignments - Mohamed, Kareem; Yousef, Mina; Medhat, Walaa; Mohamed, Ensaf Hussein; Khoriba, Ghada; Arafa, Tamer (Information systems (Oxford), 2025)
The increasing adoption of programming education necessitates efficient and accurate methods for evaluating students’ coding assignments. Traditional manual grading is time-consuming, often inconsistent, and prone to subjective biases. This paper explores the application of large language models (LLMs) for the automated evaluation of programming assignments. LLMs can use advanced natural language processing capabilities to assess code quality, functionality, and adherence to best practices, providing detailed feedback and grades. We demonstrate the effectiveness of LLMs through experiments comparing their performance with human evaluators across various programming tasks. Our study evaluates the performance of several LLMs for automated grading. Gemini 1.5 Pro achieves an exact match accuracy of 86% and a ±1 accuracy of 98%. GPT-4o also demonstrates strong performance, with exact match and ±1 accuracies of 69% and 97%, respectively. Both models correlate highly with human evaluations, indicating their potential for reliable automated grading. However, models such as Llama 3 70B and Mixtral 8 × 7B exhibit low accuracy and alignment with human grading, particularly in problem-solving tasks. These findings suggest that advanced LLMs are instrumental in scalable, automated educational assessment. Additionally, LLMs enhance the learning experience by offering personalized, instant feedback, fostering an iterative learning process. The findings suggest that LLMs could play a pivotal role in the future of programming education, ensuring scalability and consistency in evaluation. •Analyze the programming education methods of evaluating programming assignments.•Present the capabilities of LLMs in understanding and evaluating code.•Compare the performance and consistency of LLMs with human evaluators.•Discuss the usage of LLMs to improve the learning experience and educational outcomes.